Skolnieku zināšanas par veselīgu dzīvesveidu - Manika, Aija (Latvijas Universitāte, 2020)
Tēmas aktualitāti nosaka Latvijas skolnieku mazkustīgais dzīvesveids. Tam par pamatu ir vide, dzīvesveids ģimenē, informāciju tehnoloģijas risinājumi, kas iegūsts popularitāti sabiedrībā un skolēnu vidē. Darba mērķis ir izpētīt skolēnu zināšanas par veselīgu dzīvesveidu. Pētniecības uzdevumi ir veikt literatūras analīzi, izstrādāt pētījuma instrumentu, atlasīt respondentus, veikt aptauju, apkopot, analizēt iegūtos datus, izdarīt secinājumus. Darba hipotēze: lielākajai daļai skolnieku ir neveselīgs dzīvesveids un to zināšanas par veselīgu dzīvesveidu ir nepietiekamas. Galvenie rezultāti - skolēni ir informēti un, ir zināšanas par veselīgu dzīves veidu, bet anketēšana norāda, ka skolēniem ir nosliece uz neregulāru ēšanas režīmu un mazkustīgumu. Stress, vide, atpūta, miegs, kā ārējie faktori, skolēniem ir zināmi, kā veselīga dzīvesveida daļa.

Final paper theme – Student knowledge about healthy life style. The actuality of the topic is determined by the fact that the inactive lifestyle among students is growing in Latvia and is based on various factors, such as the existing and accessible environment, family lifestyle, information technology solutions, which have gained popularity in society and students. The aim of the work is to study students knowledge of a healthy lifestyle. The tasks of the research is to perform literature analysis, to develop a research tool, to select respondents, to conduct a survey, to summarize and analyze the obtained data, to draw conclusions. There is a hypothesis in the work: most students have an unhealthy lifestyle and their knowledge of a healthy lifestyle is insufficient. Research tool: questionnaire. Research method: quantitative. The main results obtained are that students are informed and have knowledge about a healthy lifestyle, but at the same time the questionnaire indicates that students are prone to irregular eating and inactive lifestyle. Stress, environment, quality rest, sleep, as external factors, in the student environment are known as part of a healthy lifestyle, but in everyday life they are not important and are not thought about. The Internet and social media are the most important sources of information in the student environment.
Student Knowledge About Healthy Life Style
Keywords: Medicīna; veselīgs; skolēni; zināšanas; dzīvesveids